The Supreme of Indonesian Language Learning Outcomes for Students through the Application of Problem-Based Learning Model - Yulianti Rasyid; Ridha Hasnul Ulya; Yenni Hayati; Asmawati Asmawati (AL-ISHLAH: Jurnal Pendidikan, 2023)
Problem-Based Learning (PBL) is one of the appropriate models developed in learning to answer the issue of increasing the quality of learning. This study aims to analyse the effect of applying the problem-based learning model in learning Indonesian general courses. This research is experimental. The sample in this study were students who took Indonesian language courses in the first semester at Padang State University. Samples for the experimental and control classes each amounted to 30 people. Data collection techniques using pretest and posttest with t-test. The instrument used was in the form of multiple choice questions totalling 30 questions which had previously been tested for the validity and reliability of the questions. From the calculation results obtained t-count (2.65) t-table (1.67). From these results, it can be concluded that the problem-based learning model significantly affects learning outcomes in Indonesian language courses.The implications of this research can assist lecturers in creating an effective and efficient learning process and can be used to shape positive student behaviour to create an academic atmosphere oriented towards 21st-century learning.